2020
DOI: 10.1161/circulationaha.119.044491
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sacubitril-Valsartan Versus Valsartan in Women Compared With Men With Heart Failure and Preserved Ejection Fraction

Abstract: Background: Unlike heart failure with reduced ejection fraction, there is no approved treatment for heart failure with preserved ejection fraction (HFpEF), the predominant phenotype in women. Therefore, there is a greater heart failure therapeutic deficit in women, compared with men. Methods: In a pre-specified subgroup analysis, we examined outcomes according to sex in the PARAGON-HF trial which compared sacubitril-valsartan and valsartan in patients with HFpEF. The primary outcome was a composite of first an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
237
3
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 308 publications
(260 citation statements)
references
References 47 publications
10
237
3
10
Order By: Relevance
“…Defining single LVEF thresholds for use is challenging given the inherent imprecision and variability in LVEF assessment and since certain subgroups (such as women) may derive benefits to a higher LVEF. 16 Costs, access, and ease of implementation will further modify the ultimate application of this therapy in HF at higher ranges of LVEF.…”
Section: Discussionmentioning
confidence: 99%
“…Defining single LVEF thresholds for use is challenging given the inherent imprecision and variability in LVEF assessment and since certain subgroups (such as women) may derive benefits to a higher LVEF. 16 Costs, access, and ease of implementation will further modify the ultimate application of this therapy in HF at higher ranges of LVEF.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the Prospective Comparison of ARNI (angiotensin receptor-neprilysin inhibitor) with ARB (angiotensin receptor blocker) Global Outcomes in Heart Failure with Preserved Ejection Fraction (PARAGON-HF) trial suggested that women might obtain more benefit than men from sacubitril/valsartan, compared with valsartan, in heart failure with preserved ejection fraction (HFpEF). [1][2][3] However, the picture is more complicated as there was also an interaction between left ventricular ejection fraction (LVEF) and the effect of sacubitril/valsartan. 2 Patients with a LVEF at or below the median (57%) seemed to gain more benefit from sacubitril/valsartan than those with a LVEF above the median.…”
Section: Interactions Between Left Ventricular Ejection Fraction Sexmentioning
confidence: 99%
“…As detailed elsewhere, the possibilities include sex-related differences in cardiac remodelling in response to blood pressure, age and other stimuli, and differences in age-related arterial stiffening, which is more pronounced in women than men. 3 Women may also have other evidence of contractile dysfunction, compared with men, for a given ejection fraction. 3 Natriuretic peptide levels are lower in women with HFpEF than in men, and women may have reduced cyclic guanosine monophosphateprotein kinase G signalling compared with men, especially after the menopause.…”
Section: Interactions Between Left Ventricular Ejection Fraction Sexmentioning
confidence: 99%
“…8 In the HFrEF trial PARADIGM-HF the benefit of sacubitril/valsartan in terms of mortality/morbidity improvement was consistent regardless of sex, whereas in the more 'nebulous' world of HFpEF, a pre-specified subgroup analysis of the PARAGON-HF trial suggested sacubitril/valsartan to reduce cardiovascular mortality/total HF hospitalizations in women but not men. 9,10 Mineralocorticoid receptor antagonists (MRAs) have IA recommendation for the treatment of HFrEF patients remaining symptomatic despite treatment with an ACEi and a beta-blocker and, among the currently used HF medications, are those which have also shown potential efficacy in HFpEF. 11 Although with the several limitations linked with the use of subgroup analyses (e.g.…”
mentioning
confidence: 99%
“…In the PARAGON-HF trial, for instance, a significant reduction in the occurrence of the primary outcome was observed in women but not in men, whereas no significant interaction between sacubitril/valsartan and sex in terms of outcomes emerged in the PARADIGM-HF trial. 9,10 Notably, the meta-analysis by Rossello et al reassures on the lack of sex-related differences in the occurrence of spironolactone-associated side effects. Perceived/actual risk of hyperkalaemia is one of the major explanations for MRA underuse in clinical practice, especially in women who are more likely to suffer from chronic kidney disease.…”
mentioning
confidence: 99%